pH-controlled complex coacervation of OSA-modified starch and chitosan with enhanced oxidative stability of flaxseed oil - Chen, Weiming; Yuan, Yirong; Zhang, Bin; Tan, Chin Ping; Huang, Qiang (Elsevier, 2025)
Understanding the effect of pH on complex coacervation is essential for designing functional oil delivery systems. This study investigated the physicochemical properties, structural characteristics, and oil-water interfacial behavior of complex coacervation between octenylsuccinic anhydride (OSA) modified starch (OSA-S) and chitosan (CS) at different pH levels, and evaluated its impact on the flaxseed oil encapsulation to improve oxidative stability. Results showed coacervation prepared at pH 6.5 exhibited the highest complex coacervation yield, lowest hydrophilicity, a more compact network structure, and enhanced thermal stability. These properties enabled effective adsorption at the oil-water interface, forming a stable coacervation layer that successfully encapsulated flaxseed oil. Consequently, the oil-microcapsules achieved the highest encapsulation efficiency (95.1 ± 0.57 %) and significantly improved the oxidative stability and storage life of flaxseed oil. These findings provide a valuable foundation for the developing pH-controlled polysaccharide-based microcapsules and the enhancing the oxidative stability of functional oils' during storage.